To stand at the Pole The Dr. Cook-Admiral Peary North Pole controversy - Hunt, William R. (Stein and Day, 1981)
Details the controversy which arose over Cook's claim that he reached the North Pole prior to Peary.
Keywords: Cook, Frederick Albert <1865-1940>; Peary, Robert E <1856-1920> - (Robert Edwin); Peary, Robert E <1856-1920> -- (Robert Edwin); Peary, Robert E. -- 1856-1920; Cook, Frederick Albert -- 1865-1940; Explorateurs américains - Biographies; Explorers -- United States -- Biography; Entdeckung; Kontroverse; Pôle Nord - Découverte et exploration; USA; North Pole; Nordpol; Biografie